FORMULATION AND EVALUATION OF ANTI-INFLAMMATORY EMULGEL OF Brucea javanica (L.) Merr SEED EXTRACTS - Handa Muliasari; Diva Almira; Windah Anugrah Subaidah (Jurnal Kimia Riset, 2022)
Anti-inflammatory drugs are needed to overcome excessive inflammatory reactions that can interfere with activities. The existence of side effects in the use of synthetic anti-inflammatory drugs causes the search for natural drugs with high therapeutic effects and low side effects to continue. Seeds of Makassar (Brucea javanica (L.) Merr) plant are known to have anti-inflammatory activity. Topical anti-inflammatory administration is currently being developed because it can minimize side effects compared to oral. This study aimed to formulate 96% ethanol extract of Makasar fruit seeds in the form of an emulgel and to determine the physical properties and anti-inflammatory activity of the emulgel in vitro. Makasar fruit seeds were extracted by sonication method using 96% ethanol solvent (3 x 35 minutes). The extract was then formulated into an emulgel preparation with an extract concentration of 1%. Emulgel was then tested for its physical properties and anti-inflammatory activity in vitro using protein denaturation inhibition method. The results showed that the physical properties of emulgel base (F0), extract emulgel (F1), and Na-diclofenac emulgel (F2) met the requirements for homogeneity, pH, adhesion, spreadability, and viscosity tests. F0, F1, and F2 had inhibition percentages of 3.74±1.58%,; 23.07±0.72%; and 33.49±0.29, respectively. According to one-way ANOVA statistical test, the three tested groups had significant differences.